Climate Change Genomics Calls for Standardized Data Reporting - Waldvogel, Ann-Marie; Schreiber, Dennis; Pfenninger, Markus; Feldmeyer, Barbara (Frontiers in Ecology and Evolution, 2020)
The advent of new and affordable high-throughput sequencing techniques allows for the investigation of the genetic basis of environmental adaptation throughout the plant and animal kingdom. The framework of genotype-environment associations (GEA) provides a powerful link by correlating the geographic distribution of genotype patterns of individuals or populations with environmental factors on a spatial scale. We coarsely review the short history of GEA studies, summarizing available studies, organisms, data type, and data availability for these studies. GEA is a powerful tool in climate change research and we therefore focus on climate variables as environmental factors. While our initial aim was to compare results of existing studies to identify common patterns or differences in climate adaptation, we quickly realized that such a meta-analysis approach is currently unfeasible. Based on our literature review we discuss the current shortcomings and lack of data accessibility which impede meta-analyses. Such meta-analyses would allow to draw conclusions on traits and functions crucial to adapt to different environmental, e.g., climate conditions, across species. We thus make a strong call for standardized data and reposition structure for GEA studies. Moreover, the coordinated documentation of candidate genes associated to environmental factors could allow the establishment of a new and additional gene ontology domain “environmental association.” This would systematically link fitness relevant genes to the corresponding environmental factor.